Psychiatric Hospitalization for Psychopathological Disorders and Self-Injurious Behaviors in Italian Children and Adolescents during COVID-19 - Maria Pontillo; Deny Menghini; Roberto Averna; Milena Labonia; Giulia Lazzaro; Maria Cristina Tata; Stefano Vicari (Children, 2023)
The evidence shows that the COVID-19 pandemic dramatically increased the number of urgent psychiatric consultations for children and adolescents in hospital emergency departments (EDs). However, what needs to be further investigated are the characteristics of psychiatric hospitalization in children and adolescents admitted to the Child and Adolescent Neuropsychiatry Unit wards in EDs. Specifically, this retrospective study aimed to examine changes in (i) the number of inpatients and (ii) the distribution of psychopathological disorders and self-injurious behaviors in our Child and Adolescent Neuropsychiatry Unit ward during the COVID-19 lockdown in Italy (March–June 2020; October 2020–January 2021) compared with the same months of previous years. We found a significantly lower number of inpatients during the first four quarantine months than the first four reference months and a higher number of inpatients during the second four quarantine months than the second four reference months. Additionally, we found an increased frequency of mood disorders, non-suicidal self-injurious behavior, and suicidal ideation during the COVID-19 lockdown compared to the reference periods. Our findings underline the need to develop psychological healthcare services for future emergency periods in order to identify and treat psychological distress in children and adolescents early, reducing the risk of psychiatric hospitalization.